IMPACT OF VOLLEYBALL PLAYERS' TRAINING MODALITIES ON SELECTED MUSCULAR STRENGTH VARIABLES: PLYOMETRIC, WEIGHT, AND COMBINATION - ADIL RASHID MALIK (RADJA PUBLIKA, 2022)
Abstract The purpose of this study was to investigate the impact of different training modalities on selected muscular strength variables among volleyball players. The study examined the effect of plyometric training, weight training, and a combination of both on muscular strength variables such as squat jump, countermovement jump, and leg press. Sixty volleyball players participated in the study and were divided into three groups: plyometric training (n=20), weight training (n=20), and combination training (n=20). The training programs lasted for eight weeks and were carried out three times per week. The results showed that all three training modalities significantly improved muscular strength variables in volleyball players. However, the combination training group showed greater improvements in squat jump, countermovement jump, and leg press compared to the plyometric and weight training groups. In conclusion, a combination of plyometric and weight training is recommended for volleyball players to enhance their muscular strength.